Classic ketogenic diet in parenteral nutrition in a GLUT1DS patient: Doing more with less in an acute surgical setting - De Giorgis, Valentina; Ferraris, Cinzia; Brena, Mario Leo; Farris, Giorgio; Gentilino, Valerio; Guglielmetti, Monica; Marazzi, Claudia; Pasca, Ludovica; Trentani, Claudia; Tagliabue, Anna; Varesio, Costanza (Frontiers in Nutrition, 2023)
Ketogenic Dietary Treatments (KDTs) are to date the gold-standard treatment for GLUT1 deficiency syndrome. Administration of KDTs is generally per os; however, in some conditions including the acute gastro-enteric post-surgical setting, short-term parenteral (PN) administration might be needed. We report the case of a 14-year-old GLUT1DS patient, following classic KDT for many years, who underwent urgent laparoscopic appendectomy. PN-KDT was required, after one day of fasting. No ad hoc PN-KDTs products were available and the patient received infusions of OLIMEL N4 (Baxter). On the sixth day postoperatively enteral nutrition was progressively reintroduced. The outcome was optimal with rapid recovery and no exacerbation of neurological manifestations. Our patient is the first pediatric patient with GLUT1DS in chronic treatment with KDT efficiently treated with exclusive PN for five days. This case reports on real-word management and the ideal recommendations for PN-KDT in an acute surgical setting.